2020
DOI: 10.1007/s11695-020-05052-8
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Diabetic Neuropathy and Nephropathy After Bariatric Surgery: a Prospective Cohort Study

Abstract: Purpose There are limited data on the impact of bariatric surgery on microvascular complications of type 2 diabetes (T2D), particularly diabetic neuropathy. We assessed microvascular complications (especially neuropathy) in obese patients with T2D before and 12 months after bariatric surgery. Materials and Methods This was a prospective observational cohort study. Measurements of neuropathy symptom profile (NSP), neuropathy disability score (NDS), vibration (VPT), cold (CPT) and warm (WPT) perception thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 34 publications
3
54
0
1
Order By: Relevance
“…The underlying pathophysiology of obesity-related peripheral neuropathy is poorly understood [12]. This study shows a signi cant reduction in central corneal nerve bre parameters in obese subjects with and without diabetes, in agreement with our previously published studies in subjects with obesity [13,23] and diabetes [5,24]. We now further report greater corneal nerve damage in the more distal inferior whorl compared to the central region providing support for a dying-back neuropathy, consistent with studies in adults [25,26] and children [27] with diabetes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The underlying pathophysiology of obesity-related peripheral neuropathy is poorly understood [12]. This study shows a signi cant reduction in central corneal nerve bre parameters in obese subjects with and without diabetes, in agreement with our previously published studies in subjects with obesity [13,23] and diabetes [5,24]. We now further report greater corneal nerve damage in the more distal inferior whorl compared to the central region providing support for a dying-back neuropathy, consistent with studies in adults [25,26] and children [27] with diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…Despite a mild neuropathy, there was signi cant distal and proximal corneal nerve loss in subjects with and without diabetes. There was also evidence of cardiac autonomic neuropathy only in obese subjects with diabetes, consistent with previous studies [23]. CCM has been used to show both progression of neuropathy in patients with type 2 diabetes over 6.5 year [5] and nerve regeneration in patients with type 1 diabetes after simultaneous pancreas-kidney transplantation [30] and in subjects with obesity with [23] and without diabetes [31] after bariatric surgery.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We and others have previously demonstrated significant small fibre damage in people with metabolic syndrome and IGT 3 , 5 , 12 . A study has shown that 11% of women with severe obesity have peripheral neuropathy 32 and we have recently reported small nerve fibre regeneration after bariatric surgery 33 .…”
Section: Discussionmentioning
confidence: 78%
“… Parameters Obese (−ve) (n = 23) Obese (+ ve) (n = 24) P Demographics Age (years) 47.4 ± 9.6 45.9 ± 9 0.9 Sex(Female/Male) 14/7 16/8 0.7 Ethnicity (Caucasian/Asian) 21/2 22/2 0.1 Smoking (no. per day) 0 2.15 ± 5.8 0.5 Alcohol (units per week) 2.3 ± 4.6 0.5 ± 1.1 0.7 Systolic BP (mmHg) 133.6 ± 22.1 126.7 ± 17.5 0.7 Diastolic BP (mmHg) 73.5 ± 11.0 71.9 ± 10.3 0.6 BMI (kg/m 2 ) 50.6 ± 8.7 48.2 ± 8.2 0.1 Number on statin therapy (%) 3 13 8 33 0.1 Number (%) metabolic syndrome 5 23 14 58 0.02 HbA1c (mmol/mol) 38.5 ± 5.9 38.0 ± 4.6 0.9 Serum triglycerides (mmol/l) 1.4 ± 0.7 1.9 ± 1.3 0.02 LDL-C (mmol/l) 2.9 ± 0.8 2.8...…”
Section: Resultsmentioning
confidence: 99%